If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 18 = 3(2a + 3) Reorder the terms: 18 + 3a = 3(2a + 3) Reorder the terms: 18 + 3a = 3(3 + 2a) 18 + 3a = (3 * 3 + 2a * 3) 18 + 3a = (9 + 6a) Solving 18 + 3a = 9 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 18 + 3a + -6a = 9 + 6a + -6a Combine like terms: 3a + -6a = -3a 18 + -3a = 9 + 6a + -6a Combine like terms: 6a + -6a = 0 18 + -3a = 9 + 0 18 + -3a = 9 Add '-18' to each side of the equation. 18 + -18 + -3a = 9 + -18 Combine like terms: 18 + -18 = 0 0 + -3a = 9 + -18 -3a = 9 + -18 Combine like terms: 9 + -18 = -9 -3a = -9 Divide each side by '-3'. a = 3 Simplifying a = 3
| X^2+12x-43=4x+5 | | -2=-7x | | -4x+6x^2+5x= | | -7.38=2.05-7.38 | | 4y+8=-2y+1 | | 24Y=72 | | 2.7+10m=7.23 | | 3a-3a^2= | | 2(x+4)+x=11 | | 16x+10=15x+2 | | 3=-4x-6 | | 1=10p | | 7(-1m)=-98 | | .36=ln(x) | | x^2=5x^2+20x+40 | | 5a+3b-6c+2a-4b+13c= | | 8(4p)=-277 | | 4x-15=3x-6 | | -13=7+4x | | 7a-a-a-a=4-a | | u^2-36=28 | | -1(-13x)=-155 | | 3x^2+5x+22=0 | | 35y+6=26 | | x*9+11=x*3+185 | | y^2-82=-1 | | 21x+105+4x+21=210 | | 3(x+4)=8(2x-2) | | j^2-144=0 | | 4p^2=8p | | 2l^2+l=15 | | 2x+-1=4 |